Surgical Management of Ventral Hernia in a Deoni Crossbred Cow - Ramya, N M; Kumar, D Dilip; Shivaprakash; Bhagavantappa , B (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Hernia is defined as the protrusion of the contents of a body cavity through a normal or abnormal opening in the cavity’s wall, either beneath the intact skin or into another adjacent cavity (Tyagi et al., 2020). There are several types of hernias that can occur in cattle; however, the most common are ventral and umbilical hernias. A ventral hernia occurs when the intestines protrude through the abdominal wall. Ventral hernia develops as a result of external forces or trauma to the abdominal wall, kick, falling on blunt object, weakening of the abdominal musculature, or rupture of the prepubic tendon or due to heavy body weight (Frank, 1981). Type of hernial contents depends on the site of hernia and most commonly the contents will be intestinal loops, mesentery, spleen or liver lobe. Diagnosis of the ventral hernia can be done by physical palpation in standing or recumbent position and radiography (Abdin-Bey and Ramadan, 2001